Teaching Teaching and learning literature in the Master’s Degree in Secondary Education Teacher Training: - Devís-Arbona, Anna; Garcia-Raffi, Josep-Vicent (Huarte de San Juan. Filología y Didáctica de la Lengua, 2022)
It is necessary to reconsider the Master’s Degree in Teacher Training in Compulsory Secondary Education, Baccalaureate, Professional Education and Language Teaching (MAES), aimed at initial teacher training in the several curricular areas, in our case, the specialty of Catalan language, at the University of Valencia. To this end, we have developed semi-open-ended response questionnaires and open-ended response texts to evaluate the fulfilment of students’ expectations after their classes on literary education and their school practices, and hence, incorporate measures to promote and improve a more adequate training of future secondary school teachers. We study the diversity among students and their conception of literary education, children’s and young people’s literature and their contents, as well as how the necessary reflection on literary education can be generated and how the future teacher can apply different tools to increase the literary competence of secondary and baccalaureate students. An analysis of the results shows that, despite the efforts made, there are still aspects that can be improved, so more reflection on them is required, not only within each specialty but also on the relationships that these specialties establish with other sections of the master’s degree (generic subjects, internships, etc.).